2014
DOI: 10.1249/jsr.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thoracic Outlet Syndrome

Abstract: Venous thoracic outlet syndrome is a relatively rare condition. One variety that is related to effort, often referred to as Paget-Schroetter syndrome, is seen more often in persons who are athletic or occupationally active. This condition can have significant morbidity if left untreated. Diagnosis is best undertaken with duplex ultrasound or venogram. The current standard for treatment includes catheter-directed thrombolysis with surgical correction of the thoracic outlet and subclavian vein with some variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Several series of cases could help understand the management of TOS in athletes. Indeed, it has been confirmed by experience-based studies and reviews ( DiFelice et al, 2002 ; Farrar et al, 2014 ). In the literature on general TOS population management, surgical approaches usually depend on the surgeons’ habits or preferences, and several surgeries have been described such as transaxillary, supraclavicular, or paraclavicular approaches.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Several series of cases could help understand the management of TOS in athletes. Indeed, it has been confirmed by experience-based studies and reviews ( DiFelice et al, 2002 ; Farrar et al, 2014 ). In the literature on general TOS population management, surgical approaches usually depend on the surgeons’ habits or preferences, and several surgeries have been described such as transaxillary, supraclavicular, or paraclavicular approaches.…”
Section: Resultsmentioning
confidence: 72%
“… Farrar et al (2014) presented in a review of literature outcomes after PSS. While they exposed few data about athletes, a consensus of return to physical training after 12 weeks was proposed after the anticoagulant treatment ending.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple provocative tests, commonly Adson and Roos tests, have been proposed in the diagnosis of ET. These tests are not routinely recommended due to their lack of specificity and high false-positive rates (3,7). When ET is suspected, it is important to first evaluate for life-threatening causes and complications of upper-extremity swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical decompression is ideally performed in a delayed manner within 14 d of diagnosis and includes a combination of first rib resection, brachial plexus neurolysis, arterial or venous reconstruction, anterior or middle scalenectomy, and/or pectoralis minor release (1,8). Oral anticoagulation is typically continued postoperatively for 3 months, although it has been suggested that treatment can be discontinued if repeat contrast venography 2 wk postoperatively displays normal patency (3,5,6,9). While noncontact rehabilitation is often begun within a month postoperatively, it is not recommended to return to contact sports until oral anticoagulation treatment is complete (10).…”
Section: Discussionmentioning
confidence: 99%